Method and system for sustainable and clean hydrogen energy using water splitting and concentrated sunlight / Abdul Syukur Abdul Rahman - Abdul Syukur , Abdul Rahman (2019)
Hydrogen has the potential to become an alternative fuel to petrol or even electricity. For decades, approximately 95% of hydrogen consumed worldwide is produced from natural gas which is burned to produce heat required for chemical reaction or to generate electricity which in turn use to carry out electrolysis process. This process does pollution by releasing carbon dioxide to the environment. This thesis is focusing more on hydrogen production using environmental friendly resources, i.e. sunlight and water. Concentrated sunlight is a key component in producing heat required to either generate electricity for electrolysis processes, or drive the endothermic chemical reactions to split hydrogen and oxygen from water. Hydrogen produced can be directly use or be stored in the storage vessel for a continuous consumption via a controlled flow rate. A stabilize pressure control where hydrogen gas is evacuated is a key component in ensuring operability and stability of end user plant operation. This research project presents methodology available in controlling the pressure of hydrogen storage vessel. . A state space approach is adopted to mathematically model the hydrogen vessel storage pressure control application. In addition, a different set of modern controllers are introduced and the system response of each controller is investigated an analysed using MATLAB and Simulink tools. The advantages and limitation of each and every modern controllers are also discussed at length. The summary of result and the recommendations are also provided in this report as reference for readers.